Self Control dalam Meningkatkan Konsistensi Belajar Akademik: Studi Mahasiswa PAI Program Magister UIN Sunan Kalijaga Yogyakarta - Muhammad Fadhil Alghi Fari Majid; Mulkul Farisa Nalva; Baharuddin Baharuddin (ILIN Institute, 2019)
Self control is one part of the individual personality aspects. Personality aspects can be in the form of beliefs, actions and attitudes. Therefore, in responding to the current of globalization, it is necessary to increase learning consistently in order to obtain good learning achievements. The purpose of this study is how self control can improve academic learning consistency. The research method used is qualitative research methods with the type of research (Field Research) or field research, data collection through data triagulation (Interview observation, and documentation). The research results obtained that the consistency of learning of each individual is based on good learning motivation, if someone has a learning motivation that tends to be good, there will always be a spirit of learning from within themselves as a need in learning to achieve learning goals. Therefore, self-control is a trait that must be realized in order to arise motivation to learn so as to increase consistent learning in students / students. So self control can move a person to do positive things including being consistent in learning because of self control, it can be said that the better the self control, the more consistent the individual is in learning.